DAMPAK KENAIKAN HARGA KEDELAI TERHADAP PENDAPATAN HOME INDUSTRI TAHU DAN TEMPE DI KOTA MERAUKE - Muhammad Abdullah Tawakal; Syahruddin Uddin (Musamus Journal of Economics Development, 2019)
The research aimed to observe the impact before and after the increase in soybean prices to income and business feasibility and Tahu in the District of Merauke. Data obtained are primary and secondary data. Total population in the research of 5 respondents Home Industry Tahuand tempeh with the sampling technique is done with all the amount of the census population sampled. The basic method used to see earnings before and after the increase in soybean prices are observation, interviewing, writing, and analysis of quantitative and qualitative descriptive hereinafter the next with the data analysis stage in the form of analysis of revenue and efficient level analysis Revenue Cost Ratio. The research result indicate that there is a price increase impact on revenues Home Industry soybean,Tahu and Tempe in the District of Merauke, while the impact contained in input factor prices, industry costs, the price of Tahu and tempeh, revenue growth entrepreneurs Tahu and tempeh. Rising soybean prices, which reached 8.8% of business Tahu and tempeh still remain profitable this is because employers make changes to the price of Tahuand tempeh, Keywords: analysis of incomeand Revenue Cost Ratio Home Industry Tahu and tempeh